Higher Pelvic Incidence Was Associated with a Higher Risk of Sagittal Malposition of Femoral Component and Poor Outcomes of Primary Total Knee Arthroplasty: A Retrospective Cohort Analysis - Li, Hongyi; Zhu, Fei; Liao, Shufen; Wang, Xiangjiang; Zhong, Yanlin; Wen, Xingzhao; Zhao, Xiaoyi; Liao, Weiming; Zhang, Zhiqi (The Journal of Knee Surgery, 2022)
Spine–pelvis–lower extremity sagittal alignment is regarded as a global sagittal balance. Currently, there are few studies evaluating the pelvic and femoral sagittal alignment during total knee arthroplasty (TKA). This retrospective study aims to elucidate how pelvic and femoral sagittal alignment affect clinical outcomes of primary TKA for osteoarthritis (OA) and determine the proper range of femoral sagittal alignment. Patient-reported outcome measures (PROMs), including the Knee Society Score (KSS), Western Ontario and McMaster Universities (WOMAC), and patient satisfaction scores, and clinician-reported outcomes (CROs), including range of motion (ROM) and pelvic and femoral sagittal parameters, of 67 cases were evaluated (89 knees) before and 1 year after TKA. The angle between the distal femur anterior cortex line and flange of the femoral component (FC) was defined as the α angle. Correlations between the α angle and PROM and CRO were investigated using multivariate and secondary regression analyses. Patients were further divided into four cohorts (A, B, C, and D) according to the α angle, and comparisons of their postoperative PROM and ROM scores were performed. Postoperative PROM and ROM scores improved significantly compared with the preoperative scores (p < 0.01). Only the α angle was significantly associated with postoperative knee extension among all PROM and CRO indexes (p = 0.001). Secondary regression demonstrated a convex upward function, and the scores were the highest at α angles of 0.57, 0.96, and −1.42 degrees for postoperative KSS, satisfaction, and range of knee extension, respectively (p < 0.01). However, the concave upward degree was the lowest at an α angle of 0.33 degrees for pelvic incidence (p < 0.001). Bonferroni's paired comparisons indicated that postoperative KSS and satisfaction of the cohort B (0 degrees ≤ α angle ≤ 3 degrees) were better than those of other cohorts (p < 0.0125). The results indicate that surgeons should pay more attention to the sagittal alignment of FC in patients with increased pelvic incidence, the distal femoral anterior cortex is recommended as an anatomic landmark, and 0 to 3 degrees might be “safe zones” of the sagittal flexion of FC in TKA. This study reflects the level of evidence III.
Keywords: osteoarthritis; total knee arthroplasty; sagittal alignment; femoral component